Carbon Storage Potential of Talang Forest in Pinggir District, Bengkalis Regency, Riau Province - Pebriandi; Defri Yoza; Wishnu Sukmantoro; Evi Sribudiani; Viny Volcherina Darlis; Sonia Somadona; Nur Suhada; Niskan Walid Masruri; Ahmad Baiquni Rangkuti (Jurnal Ilmu Ilmu Kehutanan, 2023)
The Indonesian government is committed to reducing carbon and greenhouse gas emissions through the Forestry and Other Land Uses (FOLU) Net-Sink 2030 scheme. Efforts that can be made to support the FOLU Net-Sink 2030 is by knowing the carbon storage potential in a forest area. This research aims to calculate the amount of potential biomass carbon storage in the talang forest. The methods used in this research are non-destructive sampling and destructive sampling. The method with destructive sampling for seedlings, understorey and litters, while for saplings, poles, trees and necromass with non-destructive sampling method. The calculation results showed that carbon stocks were trees (77.76 tons/ha), poles (9.56 tons/ha), saplings (7.99 tons/ha), seedlings and understorey (0.65 tons/ha), litters (1.20 tons/ha) and necromass (2.39 tons/ha). Aboveground carbon storage in the talang forest was found to be 99.56 tons/ha. The total aboveground carbon storage potential of the gutter forest was 7,933 tons of carbon.